Naphthalenetetracarboxylic diimide derivatives: Molecular structure, thin film properties and solar cell applications - Falkenberg, C; Hummert, M; Meerheim, R; Schünemann, C; Olthof, S; Körner, C; Riede, MK; Leo, K (De Gruyter, 2018)
The effciency of organic solar cells is not only determined by their absorber system, but also strongly dependent on the performance of numerous interlayers and charge transport layers. In order to establish new custom-made materials, the study of structure-properties relationships is of great importance. This publication examines a series of naphthalenetetracarboxylic diimide molecules (NTCDI) with varying side-chain length intended for the use as n-dopable electron transport materials in organic solar cells. While all compounds basically share very similar absorption spectra and energy level positions in the desired range, the introduction of alkyl chains has a large impact on thin film growth and charge transport properties: both crystallization and the increase of conductivity by molecular doping are suppressed. This has a direct influence on the series resistance of corresponding solar cells comprising an NTCDI derivative as electron transport material (ETM) as it lowers the power conversion efficiency to 1%. In contrast, using the side-chain free compound it is possible to achive an efficiency of 6.5%, which is higher than the efficiency of a comparable device comprising n-doped C60as standard ETM.